Temporal and topographical variation of subchondral bone changes in a spontaneous animal models of osteoarthritis - Ahmad Rafani, Fikri; Mohammad Subri, Abdul Hadi; Mohd Sabri, Muhammad Farhan; Robson Brown, Kate; Sharif, Mohammed; Zamli, Zaitunnatakhin (Universiti Putra Malaysia, 2015)
Background: Osteoarthritis (OA) is a common form of arthritis that affects major joint structures including the subchondral bone plate (Sbp) and trabecular bone (Tb). Previous studies have shown that the patterns of subchondral bone (Sb) changes in the medial and lateral sides of tibial epiphysis, in both human and animal models of OA are different. The aim of the current study is to investigate detailed structural changes of Sbp and Tb in sub-regions within each side of the tibia during the initiation and progression of OA in Dunkin Hartley (DH) which develop OA around 12 weeks of age and Bristol Strains 2 (BS2) guinea pigs that develop OA around 24 weeks. Methods: The micro-computed tomography (Micro-CT) images of the proximal part of the right tibia of six males DH (n=24) and BS2 (n=24) guinea pigs were obtained from previous study, and collected at 10, 16, 24, and 30 weeks of age. Micro-CT analyzer software was used to quantify the Sbp thickness (SbpTh); Tb morphometric and bone mineral density (BMD) in four sub-regions (i.e. anteromedial, anterolateral, posteromedial, and posterolateral) within each side of the tibial epiphysis. The data were then compared between anterior and posterior sub-regions, the medial and lateral sub-regions, and time points. Results: Sb changes in the four sub-regions were generally more prominent in the medial than lateral side, and in the DH than BS2. In the medial side of the tibia, the posteromedial or PMM sub-region of DH showed a significantly greater of SbpTh [PMM: 463.43